Minuman Jahe Madu Mengurangi Mual dan Muntah pada Ibu Hamil - Herlinadiyaningsih Herlinadiyaningsih; Suharyo Hadisaputro; Triana Sri Hardjanti; Ari Suwondo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The Objective of the study was to analyze the effect of ginger honey drink to the frequency of nausea and vomiting in pregnant women. Experimental studies using randomize design pre-post test control group design. In this design of research have four group which devided into three group interventions and one control. The group intervention were given honey drink, ginger, combination of ginger and honey while the control group were given vitamin B6 which given to pregnant women who experience nausea and vomiting. The results showed no statistically significant effects among the three intervention groups and a control group of the duration of nausea, frequency of nausea, vomiting frequency and the frequency of nausea and vomiting (p value0.05) (drink honey p=0.007; ginger p= 0.001, a combination of ginger and honey p=0.001) and the control group (p=0.001). Giving drink ginger and honey combination is used as one of the best options in the treatment of nausea and vomiting in pregnant women.